Análise de vibração: estudo da técnica e aplicação prática em uma indústria siderúrgica - Siemann, Gustavo Mello [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
It is known that predictive maintenance is a fundamental strategy within the proper functioning of industrial maintenance. Vibration analysis of rotating equipment is one of the monitoring techniques found within predictive maintenance. From the study of the vibration analysis technique and the presentation of a case study, the aim is to train the predictive maintenance team of the industrial plant supplying the case study. It presents a review of the fundamentals of vibration analysis and a case study applied to an electric motor of a cage in a rolling mill block in a steel industry. In the case study, a failure by BPFI in the bearing on the coupled side of the engine is identified, where the vibration analysis technique previously identified the failure and made it possible to intervene in the equipment before a breakdown. From the case study, it was possible to evidence the importance of vibration analysis for the preservation of assets critical to the process, both in the cost evidence and in the technical assertiveness available. Added to this is the relevance of predictive maintenance techniques in the future of industry 4.0, which associated with new technologies such as IoT and machine learning will represent a significant gain in efficiency and agility in industrial maintenance.

Sabe-se que a manutenção preditiva é estratégia fundamental dentro do bom funcionamento da manutenção industrial. A análise de vibração de equipamentos rotativos é uma das técnicas de monitoramento encontradas dentro da manutenção preditiva. A partir do estudo da técnica de análise de vibração e da apresentação de um estudo de caso, busca-se a capacitação da equipe de manutenção preditiva da planta industrial fornecedora do estudo de caso. Apresenta-se uma revisão dos fundamentos da análise de vibração e um estudo de caso aplicado à um motor elétrico de uma gaiola de um bloco laminador de uma indústria siderúrgica. No estudo de caso é identificada uma falha por BPFI no rolamento do lado acoplado do motor, onde a técnica de análise de vibração identificou previamente a falha e possibilitou a intervenção no equipamento antes de uma quebra. A partir do estudo de caso foi possível evidenciar a importância da análise de vibração para a preservação de ativos críticos ao processo, tanto na evidência de custo, quanto na assertividade técnica que se dispõe. Soma-se a isso a relevância das técnicas de manutenção preditiva no futuro da indústria 4.0, que associadas a novas tecnologias como IoT e machine learning representarão um ganho significativo em eficiência e agilidade na manutenção industrial.
Vibration analysis: study of the technique and practical application in a steel industry
Keywords: Predictive maintenance; Vibration analysis; Envelope analysis; Failure mechanisms; Unbalance; Misalignment; Clearance; Bearing; Gear; Manutenção preditiva; Análise de vibração; Análise de envelope; Mecanismos de falha; Desbalanceamento; Desalinhamento; Folgas; Rolamento; Engrenagem; Vibração - Medição; Controle preditivo; Motores elétricos - Enrolamento